Chitosan oligosaccharide decorated liposomes combined with TH302 for photodynamic therapy in triple negative breast cancer - Yinan Ding; Rui Yang; Weiping Yu; Chunmei Hu; Zhiyuan Zhang; Dongfang Liu; Yanli An; Xihui Wang; Chen He; Peidang Liu; Qiusha Tang; Daozhen Chen (Journal of Nanobiotechnology)
Abstract Background Triple negative breast cancer (TNBC) is an aggressive tumor with extremely high mortality that results from its lack of effective therapeutic targets. As an adhesion molecule related to tumorigenesis and tumor metastasis, cluster of differentiation-44 (also known as CD44) is overexpressed in TNBC. Moreover, CD44 can be effectively targeted by a specific hyaluronic acid analog, namely, chitosan oligosaccharide (CO). In this study, a CO-coated liposome was designed, with Photochlor (HPPH) as the 660 nm light mediated photosensitizer and evofosfamide (also known as TH302) as the hypoxia-activated prodrug. The obtained liposomes can help diagnose TNBC by fluorescence imaging and produce antitumor therapy by synergetic photodynamic therapy (PDT) and chemotherapy. Results Compared with the nontargeted liposomes, the targeted liposomes exhibited good biocompatibility and targeting capability in vitro; in vivo, the targeted liposomes exhibited much better fluorescence imaging capability. Additionally, liposomes loaded with HPPH and TH302 showed significantly better antitumor effects than the other monotherapy groups both in vitro and in vivo. Conclusion The impressive synergistic antitumor effects, together with the superior fluorescence imaging capability, good biocompatibility and minor side effects confers the liposomes with potential for future translational research in the diagnosis and CD44-overexpressing cancer therapy, especially TNBC. Graphic abstract